A case with mesenteric desmoid tumor after laparoscopic resection of stage I sigmoid colon cancer - Musashi Takada; Takashi Okuyama; Ryuji Yoshioka; Tamaki Noie; Emiko Takeshita; Shinichi Sameshima; Masatoshi Oya (Surgical Case Reports)
Abstract Background Intra-abdominal desmoid tumors are rare and generally occur in some patients with familial adenomatous polyposis or secondary to an external stimulus such as surgical trauma. We report herein a case of intra-abdominal desmoid tumor in the jejunal mesentery after laparoscopic colectomy for sigmoid colon cancer. Case presentation A 74-year-old woman underwent laparoscopic sigmoid colectomy for colon cancer with pathological stage I. Follow-up computed tomography (CT) 18 months after primary surgery showed a nodular and enhanced soft tissue density mass, 20 mm in size, in the mesentery at the left side of the abdomen. Serum carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) levels were within the normal range. Fluorodeoxyglucose positron emission tomography did not suggest cancer recurrence. Another CT scan, done 1 month later, revealed that the tumor had enlarged to 25 mm in size. Although the pathological diagnosis was not obtained, we suspected recurrence of the sigmoid colon cancer and applied chemotherapy using capecitabine, oxaliplatin, and bevacizumab. After 3 cycles of chemotherapy, however, the tumor had enlarged further. Therefore, the surgical resection of the tumor was performed to determine the diagnosis and to achieve possible curative resection of the tumor. The tumor existed in the mesentery of the jejunum, 100 cm from the ligament of Treitz, and showed invasive growth. We resected 40 cm of the jejunal segment together with the tumor. Microscopically, the tumor was composed of fibroblast, myofibroblast, and infiltrating the inflammatory cell and diagnosed as desmoid tumor by immunostaining (desmin+/−, β-catenin+, CD117−, vimentin+). At 33 months after the resection of the desmoid tumor, neither the sigmoid colon cancer nor desmoid tumor has had a recurrence. Conclusions After surgery for gastrointestinal cancer, it is difficult to differentiate between intra-abdominal desmoid tumor and recurrence. The possibility of intra-abdominal desmoid should be considered along with tumor recurrence during postoperative surveillance after resection of gastrointestinal cancer, especially when the risk of recurrence is low.